Differences between gap‐related persistent conduction and carina‐related persistent conduction during radiofrequency pulmonary vein isolation. (22nd May 2020) - Mulder, Mark J.; Kemme, Michiel J. B.; Götte, Marco J. W.; van de Ven, Peter M.; Hauer, Herbert A.; Tahapary, Giovanni J. M.; van Rossum, Albert C.; Allaart, Cornelis P.
Abstract: Background: During pulmonary vein isolation (PVI), nonisolation after initial encircling of the pulmonary veins (PVs) may be due to gaps in the initial ablation line, or alternatively, earliest PV activation may occur on the intervenous carina and ablation within the wide‐area circumferential ablation (WACA) circle is needed to eliminate residual conduction. This study investigated prognostic implications and predictors of gap‐related persistent conduction (gap‐RPC) and carina‐related persistent conduction (carina‐RPC) during PVI. Methods and Results: Two hundred fourteen atrial fibrillation (AF) patients (57% paroxysmal, 61% male, mean age 62 ± 9 years) undergoing first contact force‐guided radiofrequency PVI were studied. Preprocedural cardiac computed tomography imaging was used to assess left atrial and PV anatomy. PVI was assessed directly after initial WACA circle creation, after a minimum waiting period of 30 minutes, and after adenosine infusion. Persistent conduction was targeted for additional ablation and classified as gap‐RPC or carina‐RPC, depending on the earliest activation site. The 1‐year AF recurrence rate was higher in patients with gap‐RPC (47%) compared to patients without gap‐RPC (28%; P = .003). No significant difference in 1‐year recurrence rate was found between patients with carina‐RPC (37%) and patients without carina‐RPC (31%; P = .379). Multivariate analyses identified paroxysmal AF and WACA circumference as independent predictors of gap‐RPC, whereas carina width and WACA circumference correlated with carina‐RPC. Conclusions: Gap‐RPC is associated with increased AF recurrence risk after PVI, whereas carina‐RPC does not predict AF recurrence. Moreover, gap‐RPC and carina‐RPC have different correlates and may thus have different underlying mechanisms.